(untitled) (ModaPalavra e-periódico, 2016)
The present paperexplores new methodologies and concepts that can help in the development of fashion products and brands. For such, we underline the importance of Trends Studies and Coolhunting, which provide insights on new consumer behaviors and mindsets. The traditional approaches to the fashion system reveal a complex phenomenon where behind the object, meaning the visible manifestation of fashion,exists a symbolic construction and power relation that originates new patterns and tastes.This work begins by approachingthe fashion system, in order to proceed to Coolhunting and Fashion Studies. The objective is to present an application model based on Trends Studies for the fashion industry, with a focus on the potential for group and audience segmentation.